IMPACT OF ENGAGEMENT WITH STEM PROFESSIONALS ON SECONDARY SCHOOL STUDENTS’ ATTITUDES TOWARDS SCIENCE AND MATHEMATICS – A CASE STUDY IN KUALA MUDA, KEDAH - Ida Normaya Mohd Nasir; Syafiza Saila Samsudin; Nur Syafizan Mohd Sufter; Rosidah Ahmad (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study explores the impact of engagement with STEM professionals on the academic performance and students’ attitudes toward science and mathematics in Kuala Muda, Kedah. Data were collected through surveys assessing academic performance, attitudes on a 5-point Likert scale, and levels of interaction with scientists, engineers, mathematicians, and technologists. Results indicate that students demonstrated more positive attitudes toward science (mean = 3.67) than mathematics (mean = 3.42). A significant proportion of students rated their academic performance in mathematics and science as "mediocre," with both subjects lagging English. Engagement with engineers positively influenced attitudes toward science (p = 0.008), while interactions with scientists (p = 0.001), mathematicians (p = 0.035), and technologists (p = 0.027) significantly enhanced attitudes toward mathematics. These findings underscore the importance of involving STEM professionals as mentors to foster positive attitudes and improve academic outcomes in STEM disciplines. Future research should investigate the long-term effects of such engagements and explore targeted strategies to maximize their impact.